Investigation on compressive behaviour of tuff masonry panels - Marcari, Giancarlo (2010)
Existing buildings and cultural heritage in the Mediterranean area are commonly composed by tuff masonry made by squared or roughly squared tuff stones. The Neapolitan yellow tuff, in particular, is a high porous volcanic stone that has been widely used as a building material to forge traditional and monumental architecture in the Campania Region. Recent building codes focus their attention on the quantitative evaluation of the performance of existing structures under different limit states. In this context, it is evident that the availability of experimental data is of paramount importance for the vulnerability assessment and performance upgrading of existing tuff constructions. This paper reviews the experimental research carried out on medium-large yellow tuff masonry panels with single and multiple-leaf cross sections. The main target of the current work is to develop an extensive database on material data and mechanical properties of tuff masonry, in the light of recent test results. Based on the collected data, the reliability of available empirical-based relationships for estimation of strength and elastic stiffness of base materials and masonry was investigated. Moreover, the reference values of compressive strength and Young’s modulus given by the Instructions to the Italian Technical Code, 2009 for soft stone masonry, have been compared against available data, and the main results are presented.